Clinical Characteristics and Management of Ovarian Vein Thrombosis: A Case Series - Alsheef, Mohammed; Abuzied, Yacoub; Alosaimi, Muteb; Altamimi, Amer; Alwazna, Qusai; Almahmood, Qusai; AlBulushi, Noura Ali; Almutair, Jehan; Zaidi, Abdul Rehman Zia; Gray, Jenny; Abu-Shaheen, Amani (Frontiers in Cardiovascular Medicine, 2022)
Background: Ovarian vein thrombosis (OVT) is uncommon, occurring in approximately 1 in every 600-2000 pregnancies. It is associated with various conditions, including thrombophilia, malignancy, sepsis, intraabdominal and pelvic inflammatory conditions, pregnancy, postpartum period, and specific surgical interventions, particularly gynecological surgeries. Thus, this study aims to identify the risk factors for OVT and elaborate on the standard treatment strategies for its management. Methods: Retrospective data collection was used, our study consists of 18 patients diagnosed with OVT between 2005 and 2016; the data were collected from the Health Information Management system at King Fahad Medical City, Riyadh, Saudi Arabia using a standard format. Results: Our study found that OVT involved the right ovarian vein more often than the left and mainly occurs in women during their postpartum period. These patients' other risk factors included hypertension, diabetes, and a high body mass index (BMI). The most common presenting complaints were abdominal pain and fever. The most common treatment was the administration of enoxaparin (low molecular weight heparin) for an average duration of one to three months, which resulted in a low recurrence rate of OVT. Conclusions: Physicians should be vigilant for suspicion of OVT in female patients presenting with lower abdominal pain and fever in their postpartum period. Additionally, it is suggested to use low molecular weight heparin as initial therapy for OVT for one to three months, resulting in a high remission rate.